Carcinoma of the duodenum. Issue 744 (October 1987) - Carragher, A.; Russell, C.
Abstract : We report two patients with primary adenocarcinoma of the duodenum who underwent successful pancreatico-duodenectomy (modified Whipple operation). One patient died from an unrelated cause three years following surgery whilst the other remains well and clinically free of disease 3 years after resection. An aggressive surgical policy in patients with this rare tumour seems justified.